1996
DOI: 10.1093/hmg/5.6.727
|View full text |Cite
|
Sign up to set email alerts
|

Population screening at the FRAXA and FRAXE loci: molecular analyses of boys with learning difficulties and their mothers

Abstract: Preliminary results on a large population-based molecular survey of FRAXA and FRAXE are reported. All boys with unexplained learning difficulties are eligible for inclusion in the study and data are presented on the first 1013 tested. Individuals were tested for the number of trinucleotide repeats at FRAXA and FRAXE and typed for four flanking microsatellite markers. Mothers of 760 boys were tested to determine the stability of the FRAXA and FRAXE repeats during transmission and to provide a population of cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
127
4
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(153 citation statements)
references
References 40 publications
(57 reference statements)
21
127
4
1
Order By: Relevance
“…In addition we have reported an excess of intermediate (41-60 repeats) FRAXA alleles in a group of boys with non-specific learning difficulty, suggesting that even relatively small expansions in FMR1 may have a phenotypic effect. 16 In women who are still cycling we have demonstrated an increased level of serum FSH in the premutation group compared with controls. 13 In a small pilot study Braat et al 17 reported the hormonal profiles of nine premutation carriers under age 40 and found levels suggestive of ovarian failure in eight of them.…”
Section: Discussionmentioning
confidence: 69%
“…In addition we have reported an excess of intermediate (41-60 repeats) FRAXA alleles in a group of boys with non-specific learning difficulty, suggesting that even relatively small expansions in FMR1 may have a phenotypic effect. 16 In women who are still cycling we have demonstrated an increased level of serum FSH in the premutation group compared with controls. 13 In a small pilot study Braat et al 17 reported the hormonal profiles of nine premutation carriers under age 40 and found levels suggestive of ovarian failure in eight of them.…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, differences in FRAXA repeat distributions have been reported between several ethnic groups, even among Caucasians. 13,20,21 Furthermore, the lack of consensus about the IA range definition increases this variability among analysed populations. In the present study, we used an IA range between 45 and 54 repeats, being the same for patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…After the molecular characterization of the FRAXE fragile site and its possible implications in learning difficulties a number of special education need and development or language delayed group of children were evaluated for the presence of FRAXE expansions (Allingham-Hawkins and Ray 1995; Chan and Wong 1998; Gécz 2000; Knight et al 1996;Milà et al 1997;Murray et al 1996;Youings et al 2000). Putting all the data together, from a large sample of higher than 13,000 individuals with mental retardation/ID, only seven FRAXE full expansions were identified.…”
Section: Discussionmentioning
confidence: 99%